Hypoglycaemia manifestations and recurrent events: Lessons from the SAVOR‐TIMI 53 outcome study. Issue 7 (8th March 2017) - Cahn, Avivit; Mosenzon, Ofri; Bhatt, Deepak L.; Leibowitz, Gil; Yanuv, Ilan; Rozenberg, Aliza; Iqbal, Nayyar; Hirshberg, Boaz; Stahre, Christina; Im, KyungAh; Kanevsky, Estella; Raz, Itamar
Abstract : Hypoglycaemia is a well‐known risk associated with the use of sulphonylureas and insulin, often limiting achievement of glycaemic goals. Recognizing the precipitants and recurrence patterns of hypoglycaemic events, particularly major events, is therefore clinically important. The SAVOR‐TIMI‐53 trial was a cardiovascular outcome study of 16 492 patients allocated to saxagliptin vs placebo added to conventional care for a median of 2.1 years. Hypoglycaemic events were a prespecified outcome in the study and were defined as a symptomatic episode that recovered with carbohydrates or any recorded blood glucose <3.0 mmol/l (<54 mg/dL). A major event was defined as one that required third‐party assistance. Analysis of the features of the first hypoglycaemic event for each patient showed that a precipitant for the event was recognized by fewer than half of the patients, with the precipitant most often being a missed meal. In 40% of patients reporting major hypoglycaemic events, no precipitating factor was recognized, and in >60%, no previous hypoglycaemic event was reported during the timespan of the study, underscoring the lack of predictability of such an event.